2011
DOI: 10.1093/neuonc/nor200
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of T2 signal changes in the assessment of progression of glioblastoma according to the Response Assessment in Neurooncology criteria

Abstract: Tumor progression, as determined by both contrast-enhanced T1 and T2 sequences is more frequently diagnosed than when considering only contrast-enhanced T1 sequences. Definition of T2-progress by a 15% T2-signal increase criterion is superior to a 25% criterion. The missing correlation of T2-progress and antiangiogenic therapy supports the hypothesis of T2-progress as part of the natural course of the tumor disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 24 publications
4
63
1
3
Order By: Relevance
“…The rate of 23% found in our data is well in line with other reports [7,8,13]. Although the percentages reported by Wick et al [7] and those in our series are similar, the approach of the two studies is nevertheless different.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of 23% found in our data is well in line with other reports [7,8,13]. Although the percentages reported by Wick et al [7] and those in our series are similar, the approach of the two studies is nevertheless different.…”
Section: Discussionsupporting
confidence: 91%
“…In some patients, gliomatosis-like changes have been noted [6]. It is reassuring that a carefully matched analysis revealed that the rate of patients with T2-only PD and/or a gliomatosis-type development was not higher with bevacizumab therapy than with any other salvage therapy [7,8]. Although FLAIR-only PD is commonly perceived as a feature associated with poor survival, the impact of the finding of FLAIR-only PD on survival has never been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, determination of radiographic progression relative to the gold standard provided by histopathologic confirmation has not been validated for either the Macdonald criteria or the RANO criteria in prospectively conducted clinical trials. Nonetheless, the value of adding T2/FLAIR assessment to the Macdonald criteria remains to be determined, although preliminary evidence of benefit has been suggested previously (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Although classifying T2/FLAIR lesions based on presence of a circumscribed appearance may improve their association with patient outcome [75•], assessment of lesion morphology remains qualitative at this time. Prior attempts in direct measurement of T2/FLAIR lesions using a bi-dimensional technique in a retrospective series of recurrent GBM resulted in identification of nonenhancing progression that is predictive of subsequent enhancing tumor progression [79]. Nevertheless, among patients with recurrent GBM treated with bevacizumab, progression determined by volumetric measurements of T2/FLAIR lesions alone did not predict overall survival [80].…”
Section: Evaluation Of Non-enhancing Tumor Burdenmentioning
confidence: 99%